Integral management of residual vegetable cooking oil from restaurants on the Omar Dengo Campus of the Universidad Nacional, Costa Rica - López-Cruz, Kevin (2019)
Incorrect handling of residual oil can affect human health and cause environmental pollution. In Costa Rica, suitable quality and safety conditions for the use of fats and oils are established in Public Food Services Regulation 37308-S, which specifies criteria and good practices for frying. An investigation of the organoleptic, physical, chemical and management characteristics of residual cooking oils in five restaurants was carried out to allow integral management of these oils, based on the contents of Decree 37308-S and the Manual of Good Environmental Practices for Food Services of the Universidad Nacional. It was found that frying practices in some restaurants were performed incorrectly, and that administrators and workers in these restaurants were not familiar with the contents of Decree 37308-S. Most residual oils analyzed had levels of polar compounds higher than permitted, and the generation rates were not in agreement with the theoretical rate, indicating that optimum cooking temperatures were not being used or the residual oil is being overused or it is delivered to a third party.